BOUGHT PRIVILEGES, EDUCATIONAL SEGREGATION, STATUS AND PRESTIGE: THE ROLE AND FUNCTIONS OF ELITE SCHOOLS AND ACADEMIC CURRICULA IN RELATION TO EDUCATION JUSTICE AND EQUALITY - Beach, Dennis (2019)
The education of the poor is usually the target of global education politics for a more socially just and equal, and effective and productive society. But according to the present article the real problems in these respects are not about the education of the poor, so much as they are those of the rich upper-class and global elites, whose inheritance of social, cultural and economic power are secured in part through the reproduction in academic education of the values of bourgeois culture and the assumed superiority of its educational code: first in schools and their curricula and then in higher education and theirs. Schools and their curricula are in focus in the article. Using ethnographic and meta-ethnographic analyses an insight into a two-way relationship between the logic of action of elite schooling and the dangerous polarizations of value that can develop through social and academic segregation are presented and a critique of elite educational differentiation, segregation and socialization is given in terms of how elite schools provide skewed access to elite knowledge and future social positions for the children of the dominant socio-cultural and economic class fractions, in ways that counteract meritocracy and educational efficiency, and that also produce alarming concepts of the value of the self and other amongst their students with significant knock on effects for future democratic polity.